Towards a Sustainable Campus: Performance and Economic Analysis of a Rooftop Solar power System for an IIUM Campus Building - Aiman Hakeemi,; Moumen Idres, (International Journal of Integrated Engineering, 2026)
This study presents the design and techno-economic analysis of a grid-connected rooftop solar photovoltaic (PV) system for an IIUM campus building using PVsyst software. The system modeling accounts for key loss factors, including temperature effects, shading, soiling (dust accumulation), and inverter inefficiencies. To validate the simulation approach, results were replicated from a reference study involving a 16.2 kWp PV system. For the IIUM campus building, nine configurations were assessed, combining three rooftop areas (1,200 m², 1,400 m², and 1,600 m²) with three PV module power ratings (535 Wp, 575 Wp, and 615 Wp). Among these, Design 7 (535 Wp modules with a 1,600 m² area) demonstrated the best overall performance, delivering an annual energy output of 362,151 kWh, a payback period of 7.4 years, and the lowest levelized cost of energy at RM 0.14 per kWh.